The risks and benefits of gene drive technology - Greely, Henry (Henry Stewart Talks, 2019)
What is gene drive?, Overview of gene editing techniques, CRISPR gene drive, The limitations and benefits of gene drive, What are the risks when gene drive is successful?, What are the risks when gene drive goes wrong?, How should gene drive be controlled?